Efficacy and safety of a biosimilar recombinant human growth hormone (r-hGH Cristalia) compared with reference r-hGH in children with growth hormone deficiency (CERES study): A randomized, multicentric, investigator-blind, phase 3 trial. (October 2019) - Czepielewski, M.A.; Garret, Q.; Vencio, S.A.C.; Rassi, N.; Felicio, J.S.; Faria, M.S.; Senn, C.C.P.; Bronstein, M.D.; Cerqueira, M.J.A.G.; Neves, A.C.L.; Sgarbi, J.A.; Spinola-Castro, A.M.; et al.
Abstract: Objective: The CERES study was a randomized, multicenter, investigator-blind trial aimed to evaluate the efficacy and safety of a recombinant human growth hormone (r-hGH) developed by Cristalia, as a biosimilar product, with analytical, functional and pharmacokinetics similarities comparable to Genotropin™, in children with growth hormone deficiency (GHD). Design: A total of 135 naïve prepubertal children with GHD were recruited, of whom 97 were randomized in 14 Brazilian sites to received either r-hGH Cristalia ( n  = 49) or Genotropin™ ( n  = 48). Efficacy was evaluated considering the height standard deviation score (SDS) and growth velocity as auxological parameters, IGF-1 and IGFBP-3 were measured as pharmacodynamic parameters during 12 months treatment time. Safety was assessed by monitoring adverse events, immunogenicity, blood count with platelets, biochemical profile and hormonal levels particularly fasting glucose, insulin and HbA1C. Results: The auxological parameters and IGF-1 and IGFBP-3 levels were comparable between both groups of patients. At end of study or the 12th month treatment, the means growth velocity was 9.7 cm/year and 9.5 cm/year, for r-hGH Cristalia and Genotropin™, respectively. The ANCOVA mean difference between the groups was 0.16 cm/year to Cristalia group (CI 95% = −0.72 to 1.03 cm/year). There was no difference in adherence among the treatment groups. The safety profile was comparable between groups. Conclusions: The clinical similarity between r-hGH and Genotropin™ was demonstrated within 12 month of treatment. On the basis of comparability of quality, safety, and efficacy to the reference product, r-hGH from Cristalia can be considered a cost-effective therapeutic option for patients with growth disorders. Highlights: CERES study compared efficacy and safety profile of r-hGH Cristalia to Genotropin™. 135 prepubertal children with growth hormone deficiency (GHD) were recruited. There was a significant and similar gain in HV from baseline in both groups. No differences were found on safety profile in both groups.